Imperative Sentences in the Novel The Lost World - Risa Al Adewiya (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2020)
This research aimed to find the translation techniques used to translate the imperative sentences and the impact to the translation quality which is found in the dialogues of novel The Lost World. This research used descriptive qualitative method. The data were collected by analyzing, questioning and interviewing to the raters. The analysis was started by finding and classifying the imperative sentences based on the theory of Greenbaum and Quirk (1990). Then, analyzing the translation techniques based on the theory of Molina and Albir (2002) and analyzing the translation quality based on Nababan (2012). The researcher found 63 data of imperative sentences in novel The Lost World. There are 45 data (71,4%) imperative sentences without subject, 4 data (6,35%) of imperative sentences with subject, 2 data (3,07%) of imperative sentences with let and 12 data (19,04%) of negative imperative. The researcher also found 12 translation techniques, they are amplification 8 data (8,42%), borrowing 3 data (3,15%), compensation 5 data (5,26%), established equivalent 15 data (15,78%), linguistics amplification 2 data (2,10%), linguistics compression 7 data (7,36%), literal translation 39 data (41,05%), modulation 2 data (2,10%), particularization, 1 datum (1,05%), reduction 7 data (7,36%), transposition 2 data (2,10%), variation 4 data (4,21%) with total data 95. The result of translation quality of imperative sentences found in the dialogues of novel The Lost World is qualified or well translated with final score of translation quality is 2,83. With the 2,78 for accuracy aspect, 2,85 for the acceptability aspect and 2,91 for the readability aspect.